The Antifibrotic and the Anticarcinogenic Activity of Capsaicin in Hot Chili Pepper in Relation to Oral Submucous Fibrosis - Huang, Zoufang; Sharma, Mohit; Dave, Aparna; Yang, Yuqi; Chen, Zhe-Sheng; Radhakrishnan, Raghu (Frontiers in Pharmacology, 2022)
A burning sensation on eating spicy foods purportedly supports the role of capsaicin, an active component of chili peppers, in the etiology of oral submucous fibrosis (OSF). Although the mast cell mediators and activated P2X receptors induce a constant burning sensation through an ATP-dependent mechanism, it is the activation of the transient receptor potential vanilloid 1 (TRPV-1) receptor by capsaicin that aggravates it. The molecular basis for the burning pain in OSF is thus attributable to the activation of TRPV1. There is overwhelming evidence that confirms capsaicin has more of a protective role in attenuating fibrosis and is potentially therapeutic in reversing conditions linked to collagen accumulation. The activation of TRPV-1 by capsaicin increases intracellular calcium ([Ca2+]i), upregulates AMP-activated protein kinase (AMPK) and Sirtuin-1 (SIRT-1), to enrich endothelium-dependent vasodilation via endothelial nitric oxide synthase (eNOS). The induction of vasodilation induces antifibrotic effects by alleviating hypoxia. The antifibrotic effects of capsaicin are mediated through the upregulation of antioxidant enzymes, downregulation of inflammatory genes and suppression of new collagen fibril formation. Capsaicin also demonstrates an anticarcinogenic effect by upregulating the cytotoxic T cells and downregulating regulatory T cells through the inhibition of angiogenesis and promotion of apoptosis. Judicious administration of capsaicin with an appropriate delivery mechanism may have therapeutic benefits in reducing pain sensation, rendering antifibrotic effects, and preventing the malignant transformation of OSF. This paper provides an overview of the molecular basis of capsaicin and its therapeutic application as an antifibrotic and anticarcinogenic agent for the treatment of OSF.